RANGSANGAN PEMIJAHAN IKAN GABUS (Channa striata) MENGGUNAKAN EKSTRAK HIPOFISA IKAN GABUS - Banie Abdan Sakuro; yulisman .; muslim . (Universitas Sriwijaya, 2016)
ABSTRACT The aim of this research was to know the different of body weight ratio on spawning latency period, total eggs, percentage of fertilized eggs and percentage of hatched eggs. The research was conducted from March to April 2015 in Laboratorium Budidaya Perairan, Agriculture Faculty, Sriwijaya University and Fish Breeding Unit Batanghari Sembilan, Indralaya, Ogan Ilir. The research used experimental methode and it was arranged in a completely randomize design with four treatments and three replications. The pituitary extract induction with donor and recipient body weight ratio 1:1 (P1), 2:1 (P2), 3:1 (P3) and sintetic hormone induction (KP). The parameters observed were spawning latency period, total eggs, percentage of fertilized eggs and percentage of hatched eggs. The results showed that percentage of fertilized eggs 98.23-99.54% and percentage of hatched eggs 51.66-64.33%. The fastest of spawning latency period were showed by P3 20.47 hours while the best of total eggs were showed by P3 6,112 eggs. Â Keywords: Spawning, Pituitary extract, Ratio, Donor, Recipient